ANALYSIS OF INFLUENCE OF VARIABLE BASE ON THE QUALITY OF JAMMER SUPPRESSION WITH TIMESPACE SIGNAL PROCESSING - Piza, D. M.; Zviahintsev, E. A. (Radio Electronics, Computer Science, Control, 2014)
The features of work of noise immunity systems of coherently-pulse radar stations with discrete adaptation of weighting coefficients of an automatic compensator of active noise have been considered. The purpose of research is evaluation of effectiveness restrictions of the automatic compensator under the combined action of active and passive noise with the difference between the antenna centers of the basic and compensation receiving channels. This paper proposes a method for estimating the effect of variable base on the quality of the active suppression of jammer for different modes of radar using time-space signal processing. The analysis was made for the inter-channel phase shift at different time intervals equal to the duration of the frequency of the pack. On the example of radar 36D6 showed that interchannel phase shift in different radar modes of operation with the time-space signal processing does not allow qualitatively suppress jammer exerted on the side lobes of the antenna pattern.